Respuestas

2014-02-13T21:17:51+01:00

Lo que se tiene es una proporción.
Usando la propiedad fundamental

 c^{2} \sqrt{1+ a^{2} x^{2}} =  \sqrt{1- a^{2} x^{2}}

Elevando todo al cuadrado
 c^{4} (1 + a^{2} x^{2}) = 1 - a^{2} x^{2}

multiplicando
 c^{4} + c^{4} a^{2} x^{2} = 1 - a^{2}x^{2}

Agrupando convenientemente
 c^{4} a^{2} x^{2} + a^{2}x^{2} = 1 - c^{4}

sacando factor común
 x^{2}(c^{4}x^{2} + a^{2}) = 1 - c^{4}

Despejando x
 x^{2} = \frac{1 - c^{4}}{a^{2} c^{4} - a^{2}}

 x = \sqrt{\frac{1 - c^{4}}{a^{2} c^{4} - a^{2}}}